The Conundrum Of Crimea: To Whom It Belongs To? - Yordan Gunawan; Jamilah Arifin; Devi Seviyana; Ananda Prasetya Utami; Elfatia Ayu Kinasih (Jurnal IUS Kajian Hukum dan Keadilan, 2020)
The recent Russian-Ukrainian dispute over Crimea has been attracted wide international attention. The crisis in the territory of Crimea has been criticize by the other states and international organizations as wrongful annexation by Russia of part of the territory of Ukraine. A referendum held in Crimea and the majority of the population choose to join the Russian Federation. Nevertheless, on March 2014, according to the Ukraine Constitutional Court, only parliament of Ukraine has the authority to make a referendum. The United Nations General Assembly adopted a resolution A/RES/68/262 on Ukraine’s territorial integrity that the annexation of Crimea, declared the referendum was invalid, and appealed to the international community not to recognize changes the status of Crimea. The research aim is to analyze whether Crimea belongs to Russia or Ukraine. The study is a normative legal research with Statute Approach and Case Approach. By using qualitative descriptive method, the research uses law as a foundation of norm and done through a library research with existing journal sources, internet, and books. The result shows that the annexation by Russia was invalid under international law perspective and Crimea should belong to Ukraine.